ALEKSANDR FAYNBERG AND ABDULLA ORIPOV:A COMPARATIVE- TYPOLOGICAL ANALYSIS OF POETIC THINKING, NATIONAL IDENTITY, AND EXISTENTIAL LAYERS - ODILOVA CHAROSXON SHAVKATJON KIZI (Ta’lim innovatsiyasi va integratsiyasi, 2026)
ANNOTATION: This article provides a comprehensive comparative- typological, hermeneutic, and structural-poetic analysis of the works of two major representatives of 20th-century Uzbek poetry — Aleksandr Faynberg and Abdulla Oripov. The research examines their positions within the historical-literary context, models of poetic thinking, the transformation of the lyrical subject, the dialectics of national and universal values, imagery systems, and existential-philosophical dimensions. The scientific novelty of the study lies in interpreting Faynberg and Oripov within a unified conceptual framework, defined as the paradigms of individual- psychological poetics and national-epic poetics. The research demonstrates that although the two poets represent different aesthetic directions, their creative legacies complement each other and significantly expand the philosophical and artistic scope of Uzbek poetry.